Evaluation of Giant Miscanthus-Based Biomass Briquettes as a Sustainable Energy Source - Tsutomu Dei; Julius Agaka Yusufu; Marthina Kuri Kendom (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
This study examines the feasibility of biomass briquettes as a renewable energy source, utilizing Giant Miscanthus, sawdust, and spent coffee grounds. Recycled paper pulp serves as a binder, enhancing energy density and combustion efficiency. The briquetting process involves drying, grinding, mixing, and compressing the raw materials. Fuel characteristics were assessed through proximate and ultimate analyses, calorimetry, and thermogravimetric analysis (TG/DTA). Spent coffee grounds exhibited the highest heating value (21,370 kJ/kg), followed by sawdust (17,610 kJ/kg) and Giant Miscanthus (17,020 kJ/kg). Thermal decomposition confirmed efficient combustion, with Giant Miscanthus achieving complete combustion at 484°C and an exothermic peak at 452°C. Giant Miscanthus emerged as a promising feedstock due to its low ash content, high energy yield, and compatibility with existing infrastructure. Combining agricultural residues with non-arable crops enhances resource efficiency. This study highlights the potential of biomass briquettes to support decarbonization, energy security, and sustainable development goals by providing a viable low-carbon alternative to fossil fuels.